2015
DOI: 10.1103/physrevb.92.060502
|View full text |Cite
|
Sign up to set email alerts
|

Observation of a Raman-active phonon with Fano line shape in the quasi-one-dimensional superconductorK2Cr3As3

Abstract: We performed a polarized Raman scattering study of quasi-one-dimensional superconductor K2Cr3As3. We detect two A 1 phonons and three E phonons. One of the A 1 modes exhibits a nearly temperature-independent Fano lineshape. Based on our first-principles calculations, we ascribe this mode to the in-phase vibrations of Cr atoms within one layer. This observation strongly suggests that the magnetic fluctuations in K2Cr3As3 are coupled to the electronic structure via the lattice.PACS numbers: 74.25. Kc, 74.25.nd, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 32 publications
2
14
0
Order By: Relevance
“…While spin fluctuations could still be relevant to both these discussions, deviation from Fermi liquid behavior is certainly expected in the context of these ARPES results, which show an absence of low-energy quasiparticle excitations. The ARPES results also demand a different explanation of the anomalously large Sommerfeld coefficient [1,4], other than the picture of quasiparticles renormalized by electron-electron (or electron-phonon [31,32]) interactions. We predict that STM studies would show a similar power law behavior to our observations [33].…”
Section: Prl 118 097002 (2017) P H Y S I C a L R E V I E W L E T T Ementioning
confidence: 99%
“…While spin fluctuations could still be relevant to both these discussions, deviation from Fermi liquid behavior is certainly expected in the context of these ARPES results, which show an absence of low-energy quasiparticle excitations. The ARPES results also demand a different explanation of the anomalously large Sommerfeld coefficient [1,4], other than the picture of quasiparticles renormalized by electron-electron (or electron-phonon [31,32]) interactions. We predict that STM studies would show a similar power law behavior to our observations [33].…”
Section: Prl 118 097002 (2017) P H Y S I C a L R E V I E W L E T T Ementioning
confidence: 99%
“…Early measurements of bulk physical properties such as electrical resistivity ρ [4][5][6], electronic specific heat coefficient γ [4][5][6], bulk magnetic susceptibility χ bulk [4][5][6] and other measurements [7][8][9] suggested that K 2 Cr 3 As 3 may exhibit strongly correlated phenomena owing to Cr 3d electrons [10,11]. The nominal valence of Cr is +2.33, assuming As 3− and K + with no vacancies.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, zero-field μSR measurements show the presence of an internal magnetic field in the superconducting state, although the magnetic field is more than 100 times smaller than that observed in Sr 2 RuO 4 . Raman scattering studies of phonons with frequencies greater than 100 cm −1 also show very weak electron-phonon coupling that is too small to account for the observed superconductivity in this material [13]. In addition to these experimental observations, various first principles and Hubbard model based theoretical studies also find that a triplet superconducting state mediated by magnetic fluctuations is likely to be present in K 2 Cr 3 As 3 [14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 90%